The accidental enterprise: Ethical consumption as commerce. Issue 85 (October 2017) - Humphery, Kim
Abstract: Ethical consumption is routinely promoted as a form of individualised responsibility taking whereby citizen-consumers consciously engage in morally/politically directed purchasing decisions. This has been heavily critiqued as a neoliberal reduction of civic engagement to market choice. It has also been contested by way of a shift to problematizing the consumer as moral agent; where attention is drawn instead to networks of agential entities - advocacy organisations, certifying bodies, marketing discourses, retail spaces, packages, household routines, and so on - that configure consumption alternatives as practice and performance. In reflecting on these concerns, this paper qualitatively explores the enterprising (rather than consumer enactment) of the ethical. Drawing on a multifaceted, three-year study of alternative consumption in Australia, the paper attends to the framing of ethical enterprise through business language, to the often ambivalent deployment of various commercial models and marketing strategies in the doing of ethical business, and to how a contestatory commerce is being imagined, especially in terms of its relations to a politics of social and economic change and to a commercial mainstream. Informed by work on markets as pragmatically assembled and on the economy as multiple, emphasis is placed throughout this article on ethical enterprise as a space of political ambiguity and as a gesture towards an alternative commerce that displaces an understanding of ethical consumption as resting on the actions of the virtuous consumer.